Intraspecific hybridization of Pleurotus djamor (Agaricomycetes) for developing short duration, high-yielding improved hybrid strain - SIVADHARSHANAPRIYA, R; REVATHY, N; MANONMANI, K; RAMAMOORTHY, V; NARAYANAN, S LAKSHMI; CHANDRAMANI, P (The Indian Journal of Agricultural Sciences, 2024)
Pleurotus is a dominant genus comprising several edible species of commercial importance. In recent years, there has been a demand for developing improved strains with superior nutritional attributes. Breeding of improved strains for shorter duration, high biological efficiency that is, the total yield relative to the dry substrate weight, becomes essential to make hybrid strains economically more attractive compared to parents with improved nutritional and functional properties linked with health benefits is an emerging concept. The present experiment was conducted during 2021 and 2022 at Agricultural College and Research Institute (Tamil Nadu Agricultural University, Coimbatore, Tamil Nadu), Madurai, Tamil Nadu to develop three intraspecific hybrids, viz. K2M2, K4M4 and K7M2 with blended characters of both parents by crossing between Pleurotus djamor isolate woody-1 and P. djamor var. MDU-1. Hybrid strains K2M2 and K4M4 were found promising and produced 1st pinhead in shorter duration of 12–15 days with a total duration of 35–40 days. Hybrid K2M2 produced maximum yield of 587.66 g/500 g of paddy straw substrate on a dry weight basis with biological efficiency of 117.53% followed by K4M4. In this study the developed hybrids were subjected to determine the bioactive secondary metabolites through Gas Chromatography-Mass Spectrometry (GC-MS) and proximate composition. Analysis of secondary metabolites revealed that hybrids and parents had specific secondary metabolites at differential levels. Also proximate analysis and organoleptic evaluation revealed that hybrids possessed improved nutritional and sensory characters compared to parents. Hybrid cultivars possesses good sensory traits, better yield and shorter duration than parents have been found to increase the number of cropping cycles annually along with improved nutritional and health benefits for the benefit of mushroom farmers.